The Effect of Think-Talk-Write Strategy to The Students’ Writing Achievement of Recount Text of The Eight Grade Students of SMP Negeri 2 Siantar - Sanggam Siahaan; Miranda Sinaga; Bernieke Anggita Ristia Damanik (The Future of Education Journal, 2024)
The objective of this study was to gather empirical evidence regarding the impact of the Think-Talk-Write (TTW) strategy on students' writing performance in recount texts. This research employed a quantitative approach and utilized a quasi-experimental design. The participants were eighth-grade students from SMP Negeri 2 Siantar, specifically class VIII-1, which had 32 students in the experimental group, and class VIII-2, which also had 32 students in the control group. The total population consisted of 64 students, selected using a purposive sampling technique. The experimental group received instruction through the Think-Talk-Write strategy, while the control group was taught using communicative language teaching methods. The findings indicated that the post-test mean score for the experimental group was 82.81, compared to a pre-test mean of 50.62. In contrast, the control group achieved a post-test mean score of 70.93 and a pre-test mean of 50.12. After collecting the data, statistical hypothesis testing was conducted using the t-test formula. The analysis revealed that the t-test value surpassed the t-table value (2.30>1.670), indicating support for the alternative hypothesis (Ha). Consequently, the study concluded that there is a significant effect of the Think-Talk-Write strategy on the writing achievement of eighth-grade students at SMP Negeri 2 Siantar in recount text writing.